Exodus to public school: Parent preferences for public schools in Peru - Gregory Elacqua; Nicolás Figueroa; Andrés Fontaine; Juan Margitic; Carolina Méndez (Inter-American Development Bank (IDB), 2023)
Due to an unprecedented rise in demand, in 2020 the Peruvian Ministry of Education implemented a centralized assignment mechanism that allowed thousands of students at various levels of education to move from the private to the public sector. In this paper, we empirically explore the determinants of accepting a public school assignment and, subsequently, remaining in the public system. Specifically, we exploit the randomness in the assignment of students to new public schools to causally estimate the influence of distance on the decision to accept a public school placement, and we explore its role in the decision to remain there. We also provide insights into various determinants of parental preferences. Our findings reveal that families care about distance from home to the assigned public school as well as the relative academic and peer quality with respect to their school of origin. Parents weigh these factors differently based on their familiarity with them. Consequently, experiencing a new school environment can alter the significance of specific attributes when it comes time to decide whether to stay at the assigned school. These findings offer valuable insights into how governments can strengthen the supply of public schooling.
Keywords: A20; D12; D83; I28; 330; School Choice; Centralized Assignment Systems; Private-Public Schooling; COVID-19